Investigations on web-shear behavior of deep precast, prestressed concrete hollow core slabs - Nguyen, Thi Nguyet Hang (2021)
Shear tests were conducted on four precast, prestressed concrete hollow core (PCHC) slabs with depths ranging from 320 mm to 500 mm, resulting in two distinct modes of failure, i.e., web-shear and flexural-shear. Shear strength results of the specimens obtained from the experimental program were compared to those predicted by EN 1168 and ACI 318-14. The comparisons showed that in some instances, these codes overpredict shear capacity of the tested specimens. Furthermore, an finite element (FE) model aimed to simulate web-shear responses of PCHC slabs was developed using Abaqus/Explicit (2014). Concrete Damage Plasticity model (CDP model) was employed to model nonlinear behavior of concrete. The sensitivity of the numerical analyses was calibrated against four plastic parameters in the CDP model. The calibrations showed that web-shear behavior of PCHC slabs is not sensitive to three out of the four plastic parameters. However, the last parameter, dilation angle, significantly affects the predicted failure loads. The validity of the developed FE model was verified by 2 shear tests in the experimental program and another 8 shear tests from the literature. Parametric studies based on the verified model were then performed. The influence of design variables including concrete strength, slab geometry, and level of prestressing force, on web-shear behavior of PCHC slabs was examined. The parametric studies showed that concrete strength plays a dominant role in the web-shear performance. However, the choice of angular or smoother-surface void shapes does not lead to a noticeable difference in web-shear capacity. Besides, web-shear strength increases with web thickness. Most importantly, a high level of prestressing force increases additional shear stresses in concrete webs due to changes in strand stress within the transmission length region. In addition, it leads to higher compressive forces in concrete diagonal struts. The presence of such a higher compression force reduces the resistance in tension of concrete webs in the direction of maximum principal tensile stress. As a result, the web-shear strength of PCHC slabs decreases with increasing prestressing force.